Pengaruh Level Penambahan Tepung Ubi Kayu dan Daun Gamal Terhadap Perubahan Dimensi Dan Skor Kondisi Tubuh Sapi Bali Jantan yang Mendapatkan Rumput Gajah - I Wayan Sulendre; Marsetyo Marsetyo; Muhamad Ilyas Mumu (Mitra Sains, 2020)
Body dimension and body condition scores are important judgment indicator in fattening bulls. This experiment was done to examine the effect of supplementation level of combination of ground cassava and gliricidia leaf on the changes in body dimensions and body condidition score of bali bulls fed elephant grass. This experiment was carried out at Malonas village, Dampelas Subdistrict, Donggala District from June to September 2018. There were 30 Bali bulls with initial body weight (W) 150-200 kg and 2-3 year of age used in this experimnet. A randomized block experimental design with 5 dietary treatments and 6 replicates per treatment was employed were bulls grouped according to their weight. The dietary treatment include elephant grass ad libitum only as A (control),(A + 0,4% BW/day) C (A + 0,8% BW/day), (A + 1,2 % BW/day) and E (A + 1,6 % BW/day)(1:1) supplementation ground cassava and gliricidia leaves. The experiment lasted for 18 weeks, consisted of 2 weeks for adaptation period and 16 weeks for measurement period. Parameter consists of hip height, girth, body length, shoulder height and body condition scores. The data obtained in the study were analyzed using analysis of varians, followed by least significant differences test to analyse the differences among the treatment mean. The results exhibited that increasing level of intake of ground cassava and gliricidia leaves increased significantly (P<0.05) hip height, girth, shoulder hight and body condition scores of Bali bulls fed elephant grass. However, body length of Bali bulls was not significantly (P>0.05) by increasing intake of ground cassava and Gliricidia leaves. It was concluded that supplementation of mixtured between ground cassava and Gliricidia (1:1) at level of 1.6% BW/day, resulted the highest body dimension and body condition score of Bali bulls given elephant grass